Aerospace series. Screw, pan head, Spiral Drive Recess, coarse tolerance normal shank, medium length thread, in titanium alloy, anodized, MoS2 lubricated. Classification: 1 100 MPa (at ambient temperature)/315 °C. (8th April 2022) - British Standards Institution,
No abstract available